Coping, executive functioning, inhibitory control and decision-making in a sample of depressed suicidal patients - Tiago Medeiros; Emanuela Lopes; Gerly Macedo; Luis Monteiro (Clinical and Biomedical Research, 2014)
Introduction: Suicidal behavior has been associated with several risk factors, including depression, maladaptive coping, and neuropsychological dysfunction. This study aimed to evaluate coping orientations, executive functioning, attentional capabilities and decision-making in depressed suicidal patients.